(untitled) (Third Sector Social Economic Review, 2018)
Abstract University life is a period when young people face change and on the other hand they have to cope with personal development and social pressure. For this reason, there are many psychological, cultural and environmental factors that affect young people’s self-esteem. One of these factors is social vulnerability. The sample of the study consists of 400 students studying at Hacettepe University in 2016 - 2017 academic year and volunteering to participate in the research. Data were collected with Coopersmith Self-Esteem Inventory, Social Vulnerability Scale and demographic information form. According to the findings, 76.3% of the students were female and 23.7% of the students were male. The average age of the students is 20 (S = 1.6). Among the students, the percentage of residents in the dormitory (70.0%) is high. Correlation analysis displayed that there is a significant negative correlation at 0.01 level (r = -. 310, p <0.01) between the self-esteem scores and social vulnerability scores. The age and social vulnerability scores of the students included in the study are found to have a significant relationship with the self-esteem scores(R=.310, R2=.096, F=14.008, p<.001). Age and social vulnerability scores explained 10% of total variance in self-esteem. According to these results, it is possible to say that the level of social vulnerability scores of students is an important predictor of self-esteem